Critical success factors in implementing projects on restituted land parcels in South Africa - Whiting, Christoper Whiting (Rhodes University, Faculty of Commerce, Rhodes Business School, 2020)
Currently there is a perception in South Africa that projects undertaken on parcels of restituted land are experiencing a much higher failure than success rate. There are, however, a few projects that are reaping the rewards and uplifting their communities, as intended by the land redistribution program. One community in particular, located in Mpumalanga, called community A, is presently undertaking a development project. This development project is one of the most successful restituted land parcel projects ever in South Africa. The purpose of the study is to determine the critical success factors in this community development project that have allowed it to enjoy such high levels of success. Are these critical success factors different from the generic industry critical success factors and, if so, what are they? As informed through literature, the critical success factors focused on in this study are as follows: the influence of management, project communication, knowledge management, the role of senior management, business strategy, project success measurements, and training and development. For the empirical study, a physical questionnaire was handed to 35 management members currently employed in the community development project. The questionnaire requested the demographics of all participants and asked them to rate, using a five-point Likert scale, their perceptions of the present project activities and of the importance of the project activities mentioned in making the project successful. Participants had to indicate the extent to which they agreed with each statement in the questionnaire. The responses obtained from the survey were presented and analysed. The study found that the critical success factor "role of senior management" was the largest problem area in the restituted land development project. "Training and development opportunities" came in second, with both factor areas showing large variances. Recommendations have been given on how to address both these problematic areas in the development project and how future restituted land parcel projects can better utilize these factors to ensure successful project implementation and long-term project success.
Keywords: Community development -- Management -- South Africa; Community development -- Management -- South Africa -- Case studies; Economic development projects -- Management -- South Africa; Economic development projects -- Management -- South Africa -- Case studies; Land reform -- South Africa -- Economic aspects; Land reform beneficiaries -- South Africa -- Case studies; Restitution -- South Africa -- Case studies